Reality, literature and symbolism in the "Leyenda del Caballero del Cisne" - Celma Valero, María Pilar (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
“Leyenda del Caballero Cisne” is an integral part of La Gran Conquista de Ultramar, the fictional chronicle that narrates the 12th century Crusades to the Holy Land. Merged between the main storyline, there are several legendary episodes that help to set the genealogy of some of the most important crusade heroes. The most standing one is Godofredo de Bouillon, who conquered Jerusalem and was proclaimed king of the place. This legend takes from chapter 47 to 185 of the Libro I of La Gran Conquista de Ultramar, and its incorporations works as a hero’s genealogy explanation, in view of the fact that he is considered the Caballero del Cisne grandson; furthermore, this legend justifies the reconquest as God’s desired and planned fact. The reading of this legend gives a paradigmatic view in light of the reality-literature-symbolization tension present in many medieval works.